Stereospecific route to 5,11-methanomorphanthridine alkaloids via intramolecular 1,3-dipolar cycloaddition of nonstabilized azomethine ylide: Formal total synthesis of (+/-)-pancracine - Pandey, Ganesh; Banerjee, Prabal; Kumar, Ravindra; Puranik, Vedavati G. (Organic Letters, 2005)
[GRAPHICS] The core structure of the complex pentacyclic 5,11-methanomorphanthridine alkaloids is constructed stereospecifically in one step employing an intramolecular [3 + 2]-cycloaddition of nonstabilized azomethine ylide as the key step. The strategy is demonstrated by accomplishing the formal total synthesis of (+/-)-pancracine.

Synthesis and evaluation of 1-deoxy-8-epi-castanospermine, 1-deoxy-8-hydroxymethyl castanospermine, and (6S,7S,8R,8aR)-8-amino-octahydroindolizine-6,7-diol - Pandey, Ganesh; Dumbre, Shrinivas G.; Pal, Sujit; Khan, Mohammad Islam; Shabab, A. (Tetrahedron, 2007)
A short, versatile, and enantioselective synthesis of 1-deoxy-8-epi-castanospermine (5), 1-deoxy-8-hydroxymethyl castanospermine (6), and (6S,7S,8R,8aR)-8-amino-octahydroindolizine-6,7-diol (7) is achieved from a common template 12. The key step utilized is PET provoked amine radical cyclization of 11 to 12 in excellent diastereoselectivity. The exocyclic double bond at C-8 of the template is functionalized to obtain 5-7 as exclusive diastereomers. 1-Deoxy-8-epi-castanospermine exhibited inhibition of alpha- and beta-galactosidase and beta-glucosidase. Compounds 6 and 7 were found to be weak inhibitors of beta-glucosidase. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: 1-deoxy-8-epi-castanospermine; castanospermine; Glycosidase inhibitors

Suzuki cross-coupling and intramolecular aza-michael addition reaction sequence towards the synthesis of 1,10b-epi-7-deoxypancratistatins and their cytotoxicity studies - Pandey, Ganesh; Balakrishnan, Madhesan; Swaroop, Pandrangi Siva (European Journal of Organic Chemistry, 2008)
The development of an efficient approach to the construction of a phenanthridone is described. The convergent strategy commences with the preparation of Suzuki cross-coupling reaction precursors, arylboronic acid 12 and a-iodo enone 14, from piperonylamine (9) and (-)-D-quinic acid (10), respectively. The coupling of 12 and 19 followed by a key intramolecular aza-Michael addition produced phenanthridone 21 featuring a cis-fused B-C ring junction. The syntheses of compounds 25 and 26, both of which are C-1 and C-10b epimers of the naturally occurring potent antitumor agent 7-deoxypancratistatin (2), from 21 are elaborated in detail in this paper. The cytotoxicities of 25 and 26 were evaluated against three different cancer cell lines. Compound 26 served as a moderate growth inhibitor of THP-1 monocytic cells (GI(50) = 14.5 mu g/mL). ((C) Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2008)
Keywords: antitumor agents; Chiral pool; Cross-coupling; Intramolecular aza-Michael addition; Pancratistatin

Suzuki cross-coupling/reductive debenzyloxycarbonylation sequence for the syntheses of [c]annulated isoquinolines: application for the syntheses of pancratistatin-like isoquinolines - Pandey, Ganesh; Balakrishnan, Madhesan (Journal of Organic Chemistry, 2008)
A two-step strategy involving Suzuki cross-coupling of boronic acids with a diverse array of alpha-iodoenones followed by hydrogenation is developed for the construction of [c]annulated isoquinolines. This mild and efficient procedure is also applied to the synthesis of highly oxygenated isoquinolines.

Synthesis of polyhydroxy piperidines and their analogues: a novel approach towards selective inhibitors of alpha-glucosidase - Pandey, Ganesh; Bharadwaj, Kishor Chandra; Khan, Mohammad Islam; Shashidhara, K. S.; Puranik, Vedavati G. (Organic & Biomolecular Chemistry, 2008)
Various polyhydroxy piperidine azasugars have been synthesized from precursors 18a and 18b, obtained in both enantiomeric forms from D-ribose. Out of these polyhydroxy piperidine azasugars, 22, 39 and 20 were found to be potent as well as selective inhibitors of a-glucosidase with K(i) values ranging as low as 1.07 mu M, 16.4 mu M, and 88.2 mu M, respectively. Replacement of the hydroxy methylene moiety of 19 (K(i) 33% at 1 mM) by an amino methylene moiety (32, K(i) 36.8 mu M) showed a remarkable increase in the activity (almost 30 times). Furthermore, increasing the lipophilicity of 33 by N-alkylation with a dodecyl group (36) showed a three-fold enhancement in the activity (K(i) 217 mu M to K(i) 72.3 mu M).

Stereoselective one-step construction of vicinal quaternary and tertiary stereocenters of the 5,10b-ethanophenanthridine skeleton: total synthesis of (+/-)-maritidine - Pandey, Ganesh; Gupta, Nishant R.; Pimpalpalle, Tukaram M. (Organic Letters, 2009)
The challenging vicinal quaternary and tertiary stereocenters of the 5,10b-ethanophenanthridine skeleton are created in a single step utilizing intramolecular [3 + 2]-cycloaddition of nonstabilized azomethine ylide as the key step. The application of the chemistry is demonstrated by synthesizing (+/-)-maritidine.

Synthesis of polyfunctional quinolizidine alkaloids: development towards selective glycosidase inhibitors - Pandey, Ganesh; Grahacharya, Debasish; Shashidhara, K. S.; Khan, Mohammad Islam; Puranik, Vedavati G. (Organic & Biomolecular Chemistry, 2009)
A highly divergent route to a variety of quinolizidine alkaloids is described. The enantiomeric precursors 22a and 22b utilized for the synthesis of these alkaloids were constructed stereospecifically from the PET cyclization of the corresponding acetylene tethered alpha-trimethylsilyl amine moieties 21a and 21b, respectively, both of which were synthesised from D-ribose. The polyhydroxy quinolizidine alkaloid 7 was found to be a selective inhibitor of alpha-galactosidase with Ki 83.9 mu M. The amine analogs 18, 12 and 10 are found to be selective and potent inhibitors of alpha-glucosidase with Ki 28, 120 and 140 mu M, respectively.

Synthesis of optically pure 2,3,4-trisubstituted tetrahydrofurans via a two-step sequential Michael-Evans aldol cyclization strategy: total synthesis of (+)-magnolone - Pandey, Ganesh; Luckorse, Srikanth; Budakoti, Asha; Puranik, Vedavati G. (Tetrahedron Letters, 2010)
Synthesis of optically pure 2,3,4-trisubstituted tetrahydrofurans is described employing a two-step Michael-Evans aldol cyclization strategy. The approach is successfully applied for the total synthesis of furano lignan natural product (+)-magnolone. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: HWE reaction; Lignans; Magnolone; Michael-Evans aldol reaction; Tetrahydrofuran

Stereoselective construction of 5,11-methanomorphanthridine and 5,10b-phenanthridine structural frameworks: total syntheses of (+/-)-pancracine, (+/-)-brunsvigine, (+/-)-maritidine, and (+/-)-crinine - Pandey, Ganesh; Gadre, Smita R. (Pure and Applied Chemistry, 2012)
The core structure of the complex pentacyclic 5,11-methanomorphanthridine skeleton and the vicinal quaternary and tertiary stereocenters of the 5,10b-phenanthridine skeleton are constructed stereospecifically in one step employing intramolecular 1,3-dipolar cyclo addition of a nonstabilized azomethine ylide (AMY) generated by the sequential double desilylation of appropriate bis-trimethylsilylmethyl amines using Ag(I)F as a single-electron oxidant. The strategy is successfully applied for the total synthesis of biologically active alkaloids such as (+/-)-pancracine, (+/-)-brunsvigine, (+/-)-maritidine, and (+/-)-crinine.
Keywords: alkaloid synthesis; cycloadditions; organic synthesis; stereocontrolled synthesis

Synthesis of 2-azabicyclo[m.n.0]-alkanes and their application towards the synthesis of strychnos and stemona classes of alkaloids - Majumder, Binoy; Pandey, Ganesh (European Journal of Organic Chemistry, 2020)
2-Azabicyclo[m.n.0]alkane ring systems, the conceptual precursors towards the synthesis of Strychnos and Stemona classes of alkaloids, were synthesized from tert-butyl 2-(phenylsulfonyl)-7-aza-bicyclo[2.2.1]hept-2-ene-7-carboxylate by alkyl Grignard reaction and intramolecular cyclisation of the in situ generated ring opening product 2. The synthesized cis-hexahydroindole 3 and cis-octahydro-benzo[b]azepine 5 scaffolds were utilized to construct the advanced intermediates 25 and 35, respectively, towards the synthesis of the corresponding Strychnos and Stemona classes of alkaloids.
Keywords: alkaloids; amines; Grignard reaction; Michael addition; Natural products